ChemInform Abstract: Pd/C‐Mediated Arylation Followed by I2‐Catalyzed Hydration Strategy: Preparation of Functionalized Novel Indanone Derivatives. Issue 43 (21st October 2014) - Dulla, Balakrishna; Kolli, Sunder Kumar; Chamakura, Upendar Reddy; Deora, Giridhar Singh; Raju, R. Ramesh; Pal, Manojit
Abstract In an in vitro study, compound (IIIa) shows inhibition of phosphodiesterase type 4B and binding with this protein in silico.